2020
DOI: 10.1101/2020.01.06.895243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Background reduction in STED-FCS using coherent-hybrid STED

Abstract: Fluorescence correlation spectroscopy (FCS) is a valuable tool to study the molecular dynamics of living cells. When used together with a super-resolution stimulated emission depletion (STED) microscope, STED-FCS can measure diffusion processes at the nanoscale in living cells. In twodimensional (2D) systems like the cellular plasma membrane, a ring-shaped depletion focus is most commonly used to increase the lateral resolution, leading to more than 25-fold decrease in the observation volumee, reaching the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Finally, the impact of tilt, which in this situation corresponds to a misalignment between excitation and depletion foci, is useful to be assessed to estimate the impact of chromatic aberrations 25 or thermal and mechanical drift. 19 We found that 2D-STED was the most sensitive to tilt, followed by z-STED and CH-STED, which can be linked to the respective sizes of their central areas, with a smaller central area leading to a higher vulnerability to misalignment (Figure 6f).…”
Section: ■ Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Finally, the impact of tilt, which in this situation corresponds to a misalignment between excitation and depletion foci, is useful to be assessed to estimate the impact of chromatic aberrations 25 or thermal and mechanical drift. 19 We found that 2D-STED was the most sensitive to tilt, followed by z-STED and CH-STED, which can be linked to the respective sizes of their central areas, with a smaller central area leading to a higher vulnerability to misalignment (Figure 6f).…”
Section: ■ Resultsmentioning
confidence: 80%
“…To assess the robustness of STED-FCS measurements with different confinement modes, we used the wavefront shaping capabilities of the SLM to quantify the effects of optical aberrations introduced as loworder Zernike modes, which had previously been reported to be most often present while imaging common biological specimens. 22 We introduced either 0, 0.5, or 1 rad rms of each mode using the SLM, corresponding respectively to no aberrations, to the maximum amplitude of aberrations we experienced in our microscope across this study (see Supporting Information, Figure S5) and to highly aberrating situations that can be encountered, for instance, when focusing deep inside a medium with a refractive index mismatch 19 or when focusing deep through an optically inhomogeneous specimen. For each aberration value, we acquired a set of STED-FCS measurements of freely diffusing Abberior Star Red dye in a water/glycerol solution.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed the procedure in [ 29 ] to align the SLM in the depletion branch. Note that, since the beam is reflected twice over the SLM at and , it accumulates static aberration due to both of these distinct locations over the SLM window.…”
Section: Description Of the Custom-built Sted Microscopementioning
confidence: 99%